ISOLASI DAN SELEKSI BAKTERI PENGHASIL BIOSURFAKTAN DARI SAMPEL LUMPUR MINYAK, KALIMANTAN TIMUR - Sari, Martha; Afiati, Fifi; Kusharyoto, Wien (Universitas Sebelas Maret, 2014)
Abstract- A total of six bacteria isolated from waste of oil sludge in the area of East Kalimantan were examined to confirm the ability in biosurfactant activity. The active compounds from each bacteria were subjected to screening test of biosurfactant by usingcanola oil as substratein fermentation system. The present study aims to evaluatedthe initial potency ofbiosurfactant producing bacteria from sludge oil in East Kalimantan. All of the isolates were confirmed as producers of biosurfactants with diverse of emulsification activity. Strain SMF4 showed the highest emulsification activity and oil displacement test within 9 days of cultivation.The screening results revealed that the six strains of sludge oil bacteria gave good values in emulsification and oil displacement activity.Â Keywords: oil sludge, six bacteria, emulsification, and biosurfactant